Extraction of Spear Grass (Imperata cylindrica) as Pro-Oxidant in Polymer Blends - Nor Azrah Abdul Halim (School of Bioprocess Engineering , Universiti Malaysia Perlis, 2017)
To identify the best extraction method (cold extraction, hot extraction, or PHWE) to extract content of spear grass. To screen the different part of spear grass (leaf, straw, root) that contribute to the highest amount of ferum (Fe) and zinc (Zn). To optimize the temperature, extraction time, and sample-to-solvent ratio for extraction of selected part by using pressurized hot water extraction (PHWE). To prove that spear grass can act as pro-oxidant to accelerate the degradation of polymer.